From Disorder to Efficiency: Implementing the 5S Method in XYZ Store Warehouse - Juwono, Ryan Marchellous; Fitriani, Katlea (UPT Publikasi Ilmiah UNISBA, 2025)
XYZ store is one of the Muslim fashion retailers that sells various kinds of Muslim equipment in Cianjur. Therefore, this research has the aim that all problems at the XYZ store can be resolved so the root cause analysis must first be carried out with a fishbone diagram and the application of the solution with the 5S method in the XYZ store warehouse area. The type of research conducted is applied research with the aim of using the 5S theory to solve problems that occur at XYZ stores. In this research, the data collection technique carried out is qualitative, where data collection is collected through interviews and direct observation. The research conducted is descriptive research that will be used to explain the fishbone analysis, the application of the 5S method, and the evaluation of the application. After the implementation of 5S, there is a considerable difference between before and after the implementation. Nevertheless, there is a problem where employees still do not follow the rules several times. Therefore, the author suggests that the store owner will more regularly check the implementation of the 5S.